2001
DOI: 10.1021/ma001782j
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Poly(amidoamine) Dendrimers and Their Complexes with Cu2+ by Matrix-Assisted Laser Desorption Ionization Mass Spectrometry

Abstract: Hydroxyl-terminated poly(amidoamine) (PAMAM) dendrimers of generation 2-4 (Gn-OH, n ) 2, 3, and 4; M r ∼ 3.7, 6.9, and 14.3 kDa, respectively) and dendrimers encapsulating Cu 2+ ions have been investigated by matrix-assisted laser desorption ionization time-of-flight (MALDI-TOF) mass spectrometry. Umbelliferone (7-hydroxycoumarin) and 2′,4′,6′-trihydroxyacetophenone (THAP) were used as the matrices for dendrimers with and without Cu 2+ in the interior. The MALDI-TOF results provide accurate molecular weight de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
89
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 70 publications
6
89
0
1
Order By: Relevance
“…A spectrum showing the full assignments of the PAMAMG2OH dendrimer and defect ions is included in Supplementary Material section Figure S-1 (which can be found in the electronic version of this article). Because the abundance of the dendrimer defect species do not change with the severity of the ESI conditions and similar defects have been observed in past MALDI [30,31] and ESI [28] studies, we speculate that these defects are present in the original dendrimer samples and do not arise from the ESI process. It has been previously shown that the types of defects observed in Figure 2 result from the retro-Michael decomposition reactions that occur in the dendrimer solutions [33].…”
Section: Analysis Of Silver Ion Complexes By Esi-mssupporting
confidence: 73%
See 1 more Smart Citation
“…A spectrum showing the full assignments of the PAMAMG2OH dendrimer and defect ions is included in Supplementary Material section Figure S-1 (which can be found in the electronic version of this article). Because the abundance of the dendrimer defect species do not change with the severity of the ESI conditions and similar defects have been observed in past MALDI [30,31] and ESI [28] studies, we speculate that these defects are present in the original dendrimer samples and do not arise from the ESI process. It has been previously shown that the types of defects observed in Figure 2 result from the retro-Michael decomposition reactions that occur in the dendrimer solutions [33].…”
Section: Analysis Of Silver Ion Complexes By Esi-mssupporting
confidence: 73%
“…The characterization of these complexes is a key aspect in understanding the relationship between the dendrimer structure, the dendrimer/metal ion complex, and the resulting dendrimer-encapsulated metal nanoparticles. MALDI-TOF mass spectrometry was used to examine the binding of Cu 2ϩ to hydroxyl terminated dendrimers [30], and in a recent study, we examined the binding of silver ions to G1 PAMAMNH 2 dendrimers using electrochemical, spectroscopic, and mass spectrometric techniques [32]. ESI-MS was used to determine Ag ϩ / PAMAM dendrimer binding stoichiometries at equimolar concentrations [32].…”
mentioning
confidence: 99%
“…As the efforts to synthesize and manufacture various dendrimers intensify, the quality control and characterization of various dendritic macromolecular materials still offers challenges. Dendritic polymers are often talked about as close-to-perfect structures, but practical samples should be handled as narrow size-distribution and charge-distribution polymers [16]. In addition to the routine chemical analysis methods (UV-vis, Fourier transform infrared (FTIR), and NMR), numerous methods have been employed for the characterization of PAMAM dendrimers including potentiometric titration, scattering methods (small-angle Y-ray scattering (SAXS), small-angle neutron scattering (SANS), dynamic light scattering), SEC, HPLC, ESI-MS and MALDI-TOF-MS methods [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yamamoto and co-workers used matrix-assisted laser desorption/ionizationtime of flight (MALDI-TOF) MS to measure the size of Rh DENs synthesized in G4 DPA dendrimers. 54 Unfortunately, we have been unable to obtain informative spectra of DENs synthesized in PAMAM dendrimer using either MALDI-TOF 98 or electrospray ionization MS. In fact, obtaining reliable MS spectra for high-generation PAMAM dendrimers, even in the absence of an encapsulated nanoparticle, is challenging.…”
mentioning
confidence: 99%